Pengaruh Brand image dan Flash sale Terhadap Keputusan Pembelian Pada Aplikasi Tokopedia (Survey Pada Followers Tiktok Tokopedia) - Muhammad Rizqi Shihab; Salim Siregar (Jurnal Ilmiah Wahana Pendidikan, 2023)
Technological developments continue to occur very rapidly. Ease of access to information has a positive impact on society. The Internet has developed a business model where previously conventional trading has become electronic. This development created the emergence of marketplaces in Indonesia. In this study discusses the influence of brand image and flash sales on purchasing decisions. This study discusses the Tokopedia’s marketplace where the object of research is Tik tok Tokopedia's followers. This study uses multiple linear regression analysis with SPSS and Excel tools. The results of the study show that there is a partial or simultaneous influence between brand image and flash sale variables on purchasing decision variables.